A Financial Feasibility Study of New Product Line Healthy Children Food Business: Case Study of Lil'bites - Tantuayo, Fairuuz Fawwas Alfarizi; Afgani, Kurnia Fajar (Integrasi Sains Media, 2024)
Based on data from the Indonesian Nutrition Status Survey (SSGI) in 2022, 21.6% of Indonesian children suffer from wasting 7.7%. A disorder known as